2010
DOI: 10.1503/cmaj.091113
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for functional recovery after stroke: a systematic review of sham-controlled randomized clinical trials

Abstract: Background: Acupuncture is frequently advocated as an adjunct treatment during stroke rehabilitation. The aim of this review was to assess its effectiveness in this setting. Methods:We searched 25 databases and 12 major Korean traditional medicine journals from their inception to October 2009. We included randomized controlled trials, with no language restrictions, that compared the effects of acupuncture (with or without electrical stimulation) with sham acupuncture. We assessed the methodologic quality of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 24 publications
1
55
0
1
Order By: Relevance
“…Several other systematic reviews assessing the effects of acupuncture for stroke have been published. 20,21 Most of them focused on the recovery of general status after stroke in rehabilitation, as measured by the Barthel Index, Nottingham Health Profile, or Scandinavian Stroke Scale. There were several limitations in the evidence showing an effect of acupuncture for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Several other systematic reviews assessing the effects of acupuncture for stroke have been published. 20,21 Most of them focused on the recovery of general status after stroke in rehabilitation, as measured by the Barthel Index, Nottingham Health Profile, or Scandinavian Stroke Scale. There were several limitations in the evidence showing an effect of acupuncture for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria drafted by the authors were used in 10 reviews, (10,24,26,27,29,31,41,(46)(47)(48) which usually contained randomization, concealment, blinded, dropout, and ITT analysis. Fourteen reviews used Cochrane risk of bias tool, (11,20,22,23,25,28,30,33,36,37,(42)(43)(44)(45) and 2 reviews also used PEDro. (28,43) Jadad scale was used in 8 reviews.…”
Section: Methodological Quality Of Systematic Reviewsmentioning
confidence: 99%
“…Some systematic reviews and meta-analyses found acupuncture to be effective, 7,9 while others did not. 6,8 It is hoped that this study will contribute to the favoring of acupuncture treatment in future meta-analyses for this population.…”
mentioning
confidence: 96%
“…5 Acupuncture is often used as an adjunct to standardized rehabilitation treatments after stroke, but its mode of action in the rehabilitation of these patients is yet to be discovered. [6][7][8][9] Acupuncture influences cerebral blood flow in healthy persons [10][11][12] and patients with stroke. 13,14 However, few studies on cerebral blood flow in patients after stroke have used sham acupuncture.…”
mentioning
confidence: 99%